Internalisasi Nilai-Nilai Luhur Pancasila Melalui Pengenalan dan Pemantapan Profil Pelajar Pancasila di SMP Negeri 5 Padangsidimpuan - Marzuki, Marzuki Ahmad; Sabri, Sabri; Lubis, Ilham Sahdi; Angin, Toras Barita Bayo; Ilahi, Afdhal; Nasution, Dwi Putria; Safitri, Adek (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Strengthening the Pancasila student profile is an important effort to instill Pancasila values in the younger generation, especially among junior high school students. This community service aims to introduce and strengthen junior high school students' understanding of the Pancasila student profile. Community service activities are carried out through the socialization of the values of the Pancasila student profile with the Participatory Action Research (PAR) model. The methods used are lectures, discussions, and practices of implementing Pancasila values in everyday life. The subjects of this activity involved 56 grade VII students of SMP Negeri 5 Padangsidimpuan. The community service activities carried out showed that there was an increase in student responses to the Pancasila profile after the socialization activities were carried out. Furthermore, it can be observed that in the socialization activities carried out, students were enthusiastic in participating in the socialization and understanding the concept of the Pancasila student profile. Students can identify and explain the six dimensions of the Pancasila student profile, namely having faith, being devoted to God Almighty and having noble character, being globally diverse, having critical thinking, being independent, and working together. In addition, students are also able to provide examples of the application of Pancasila values in everyday life.